Genetic Evaluation of Pepper Mild Mottle Virus as an Indicator in Water Quality Monitoring and Human Fecal Contamination in Swedish Waters - Marianela Patzi Churqui; Fredy Saguti; Timur Tunovic; Ambjörn Kärmander; Martin Lagging; Kristina Nyström; Hao Wang (Food and Environmental Virology, 2026)
Pepper mild mottle virus (PMMoV) has emerged as a promising viral indicator for human fecal contamination and evaluating viral removal efficiency in water treatment systems. However, few studies have examined this potential from a genetic perspective over extended timescales. This study investigated PMMoV presence and genetic diversity across multiple water environments in Sweden, including wastewater, lake water, and raw water used for drinking water production, collected between 2016 and 2024. PMMoV was consistently detected in both wastewater and lake water, showing relatively stable concentrations in wastewater between years, and with levels typically 4–7 log₁₀ higher than in lake water. Comparative genotyping of the coat protein (CP) and replication-associated (RP) regions for wastewater samples showed no significant differences. We successfully sequenced 67 isolates from wastewater, 16 from lake water, and 2 from source water at the CP region. Sequence analysis revealed extremely high nucleotide identities (> 96%) with minimal divergence between samples collected six years apart or from different water types. Phylogenetic comparisons with global reference sequences confirmed high genetic conservation worldwide. These findings demonstrate the remarkable genetic stability of PMMoV over time and geography, supporting its reliability as a viral process indicator for water treatment systems. However, the potential for PMMoV to originate from non-human sources suggests it should not be used as a standalone marker for human-specific fecal contamination. Overall, this study highlights the global genetic conservation of PMMoV and its utility for long-term environmental surveillance and water quality assessment.

Influence of viral load on severity and mortality in COVID-19 - Johan Ringlander; Anna Martner; Li Huiqi; Magnus Gisslén; Magnus Lindh; Johan Westin; Fredrik Nyberg; Martin Lagging; Staffan Nilsson; Kristoffer Hellstrand (Infectious Diseases, 2025)

Remdesivir is active in vitro against tick-borne encephalitis virus and selects for resistance mutations in the viral RNA-dependent RNA polymerase - Kristina Nyström; Edward Trybala; Joanna Said; Anette Roth; Marianela Patzi Churqui; Ambjörn Kärmander; Tomas Cihlar; John P. Bilello; Tomas Bergström; Martin Lagging (Infectious Diseases, 2025)

Catch-up antibody responses and hybrid immunity in mRNA vaccinated patients at risk of severe COVID-19 - Samer Al-Dury; Jesper Waldenström; Johan Ringlander; Sigrun Einarsdottir; Markus Andersson; Hevar Hamah Saed; Johan Waern; Anna Martner; Kristoffer Hellstrand; Martin Lagging (Infectious Diseases, 2023)

Measures against COVID-19 affected the spread of human enteric viruses in a Swedish community, as found when monitoring wastewater - Hao Wang; Marianela Patzi Churqui; Timur Tunovic; Lucica Enache; Anette Johansson; Magnus Lindh; Martin Lagging; Kristina Nyström; Heléne Norder (Science of The Total Environment, 2023)

Sofosbuvir/velpatasvir for the treatment of HCV: excellent results from a phase-3, open-label study in Russia and Sweden - Vasily Isakov; Vladimir Chulanov; Dzhamal Abdurakhmanov; Eduard Burnevich; Elena Nurmukhametova; Galina Kozhevnikova; Natalya Gankina; Sergey Zhuravel; Svetlana Romanova; Robert H. Hyland; Sophia Lu; Evguenia S. Svarovskaia; et al. (Infectious Diseases, 2019)

Treatment of hepatitis C virus infection for adults and children: updated Swedish consensus guidelines 2017 - Martin Lagging; Rune Wejstål; Ann-Sofi Duberg; Soo Aleman; Ola Weiland; Johan Westin (Infectious Diseases, 2018)

Treatment of hepatitis C virus infection: updated Swedish Guidelines 2016 - Martin Lagging; Rune Wejstål; Gunnar Norkrans; Olle Karlström; Soo Aleman; Ola Weiland; Maria Castedal; Johan Westin (Infectious Diseases, 2017)

Treatment of hepatitis C virus infection for adults and children: Updated Swedish consensus recommendations - Martin Lagging; Rune Wejstål; Gunnar Norkrans; Olle Karlström; Soo Aleman; Ola Weiland; Maria Castedal; Filip Josephson (Infectious Diseases, 2016)